Photoluminescent Anisotropy Amplification in Polymorphic Organic Nanocrystals by Light-Harvesting Energy Transfer - Sun, Meng-Jia; Liu, Yingying; Zeng, Wei; Zhao, Yong Sheng; Zhong, Yu-Wu; Yao, Jiannian (Journal of the American Chemical Society, 2019)
Polymorphism and anisotropy are fundamental phenomena of crystalline materials. However, the structure-dependent photoluminescent (PL) anisotropy in polymorphic organic crystals has remained unexplored. Herein, two polymorphic nanocrystals, green-emitting nanorods (PtD-g) and yellow-emitting nanoplates (PtD-y), were obtained from a platinum(II)−β-diketonate complex. The PtD-y crystals display remarkable PL anisotropy with an anisotropy ratio of up to 0.87 whereas the emission of the PtD-g crystals is nearly unpolarized. The polarization properties are rationalized on the different molecular packing of these crystals. By light-harvesting energy transfer, the PtD-y crystals are successfully used to amplify the emission polarization of a red-emitting platinum acceptor (PtA) doped into the donor crystalline matrix, which is otherwise weakly polarized as pure crystals.